Interaction of endophytic microorganisms with respect to cypermethrin - L. R. Valiullin; E. V. Skvortsov; V. I. Egorov; L. N. Alekseyko; S. V. Klimovich; I. E. Pamirsky; A. F. Artemenko; A. M. Zakharenko; K. S. Golokhvast (Юг России: экология, развитие)
Aim. Search and selection of microorganisms with active enzymatic properties for possible biodestruction of pyrethroids.Materials and Methods. For effective screening and selection of the most active isolates, for the subsequent development of biotechnological methods for the destruction of pesticides and reduction of their toxicity, samples of the phylosphere and rhizosphere of agricultural crops, food products, etc. were taken. The isolates were evaluated by intracellular metabolism and the production of exoenzymes. The isolated microorganisms were identified on the basis of the "Bergi Bacteria Determinant". Screening of microorganisms for the development of biotechnological methods to reduce the toxicity of ecotoxicants included the following stages: selection of sources, sampling, seeding on a dense medium for isolation of pure culture, replanting of pure culture and investigation of biological properties of isolated strains.Results. In order to search for microorganisms capable of utilising pyrethroids, isolates of microscopic fungi and bacteria were obtained. Of the 23 selected strains, 12 had the widest spectrum of activity, while 5 strains showed the most pronounced and stable antagonistic activity against pathogenic microorganisms at various temperature parameters from 30°C to 42°C (Escherichia coli, Enterococcus faecalis, Pseudomonas aeruginosa, Staphylococcus aureus). For the selected strains, the environment was optimised to activate cellular metabolic processes. The activity of amylases, proteases, xylanases and cellulases of the fungus Trichoderma, and proteases of L. plantarum, L. lactis,   B. subtilis and Propionibacterium was evaluated. Studies of the effect on the synthesis of hydrolytic enzymes of various concentrations in the culture medium in the presence of xylan polysaccharides, cellulose, starch and casein protein were carried out.Conclusion. Toxicological studies of the selected isolates and of a composition consisting of these isolates in the form of a culture suspension on the simplest stylonychia were carried out. Biotesting on isolated aquatic microorganisms (Trichoderma, L. plantarum, L. lactis, B. subtilis and Propionibacterium) showed that the percentage of dead infusoria (S. mytilus) in both the experiment and the control showed no significant differences. A microbiological composition has been created that can be used to protect the environment when exposed to toxicants of agrotechnogenic origin. The selected strains were tested for the possibility of biodegradation of pyrethroids using the example of cypermethrin.